Pengaruh Kepemimpinan Primal Dan Motivasi Terhadap Disiplin Serta Dampaknya Pada Kinerja Pegawai Di Lingkungan Sekretariat Daerah Kota Bekasi - Eka Febriyanti; Derriawan; Widarto Rachbini (CV ODIS, 2020)
The purpose of this study is to determine how much influence primal leadership and motivation on discipline and effect of performance employee in Sekretariat Daerah Kota Bekasi. The research method used is quantitative research in the form of a survey. Samples of this research are 136 employees. Methods of data collection using questionnaires with Likert scale. The research results obtained data from the five formulas discussed, namely: (1) primal leadership influence on performance; (2) motivation influence on performance; (3) primal leadership influence on discipline; (4) motivation influence on discipline; (5) discipline influence on performance.